Physicochemical parameters and mineral components in Vietnam honey as a promising tool for classifying biological origin of honeys - Thu Huong Nguyen; Thanh Long Ngo; Huu Quang Nguyen (Vietnam Journal of Science, Technology and Engineering, 2021)
For many years honey is known as a natural sweetener agent with high nutritional value and brings many health benefits, the desirable flavor and medicinal properties of premium honey make it highly desirable. Because of this perticular reason, honey has been a target of adulteration through the mixing of low-quality honey and mislabelling of the honey’s origin. Vietnam was ranked the sixth largest in the world and the second largest in Asia in the amount of honey exported in 2018. The aim of this research considers the potential of using mineral and physicochemical data to authenticate the origin of honey. To this end, 40 samples of 8 botanica collected from 18 different regions of Vietnam were analysed for its metal contents (Na, K, Mg, Ca, Al, Cu, Fe, Mn, Zn, Pb, Cd, Ni, Cr, Co, As, Hg) and physicochemical parameters (pH and electrical conductivity). The data were processed by multivariate analysis, which allowed the classification of honey according to its botanical origin.